Implementation of web product search engine (Part I) - Wong, Sunny Sin Chun. (2012)
Online shopping is gaining popularity as the preferred mode of shopping as opposed to being physically at a shop. This mode is also preferred because it reduces the amount of time needed to purchase products by allowing the users to quickly perform a search on their items of choice without having to window shop through an entire shopping mall.